Swot of students’ leadership in higher learning / Zaidatul Shakila Mohamad Ashari and Zulfadli Mahfodz - Mohamad Ashari, Zaidatul Shakila; Mahfodz, Zulfadli (Universiti Teknologi MARA, Sabah, 2023)
Nurturing undergraduate student leaders has become a priority in higher learning as it is beneficial for the students, institutions, employers, and society. Even though there are numerous initiatives for developing and educating student leaders, there is a need for fundamental studies on what student leaders perceive leadership to be, and the situations in which they would view it as crucial. The purpose of this article is to share the SWOT analysis report that was used to evaluate student leadership’s internal strengths and weaknesses, together with the external opportunities and threats. Structured open-ended survey questions were given to 78 student leaders during a leadership camp from a public university in Perak, Malaysia. Qualitative content analysis concept was used for the SWOT analysis. The core premise of a SWOT analysis based on the result must be taken into account for the leaders to better formulate a successful strategy, and for the planning of direction after carefully assessing the strengths, weaknesses, threats, and opportunities.